Coronary Microvascular Dysfunction - Doharjo Manullang; Imran Soleh; Rukiah Chodilawati; Syamsu Indra; Ferry Usnizar; Erwin Sukandi; Taufik Indrajaya; Ali Ghanie (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Coronary microvascular dysfunction (DMK) is a condition of patients who are accompanied by complaints of chest pain where the results of coronary angiography examination are normal and this is almost 49% with 60% of patients diagnosed with DMK. Another study said that about 40% of patients with DMK showed coronary flow reserve (CFR <2) of about 40% and the WISE study (Women's Ischaemia Syndrome Evaluation) showed that about 47% of patients with chest pain had normal coronary arteries. DMK can be divided into 4 groups; DMK with no coronary arterial disease (CAD) obstruction and myocardial disease, DMK with myocardial disease where this occurs due to remodeling of intramural coronary arteries, DMK with CAD (coronary arterial disease) or acute myocardial infarction with or without ST segment, iatrogenic typhoid DMK occurs after coronary recanalization caused by vasoconstriction and distal embolization. The mechanism of action of DMK can be caused by several factors, namely endothelial dysfunction, smooth muscle dysfunction, decreased diastolic perfusion time, damage to blood vessels and damage to the vascular and microvascular remodeling. And to enforce this DMK, there are several tests carried out in diagnosing the disease, some of which are invasive and non-invasive so that by enforcing the diagnosis of this disease, treatment for DMK can be done immediately and optimally.